Costs and Effects of Left Atrial Venous Drainage Cannula Placement in Veno-Arterial ExtraCorporeal Membrane Oxygenation (LAVA ECMO) via Transeptal Puncture for Left Heart Decompression - A Single Institution Case Series (Global Journal of Medical Research, 2023)
Abstract not found
Keywords: ECMO; cardiogenic shock; myocardial recovery